Evangelische Grab- und Gedenkkultur zum Ersten Weltkrieg in Württemberg: der Verein für christliche Kunst - Schilling, Jörg (RIHA Journal, 2017)
The mission of the Verein für christliche Kunst in der evangelischen Landeskirche Württembergs, founded in 1857, was to advise Protestant parishes on aesthetic questions. During WW1 it started to focus not only on graves and memorials but increasingly also on symbolic forms like medals and decorations. The association instructed architects to design ideal examples and standard models. The intention was to prevent both cheap industrial production and exaggerated pathos. By avoiding graphic representations of Christian virtues and by providing more homogeneous and simple designs, it hoped to strengthen the corporate feeling of the Protestant community.